1991
DOI: 10.1016/0010-2180(91)90204-o
|View full text |Cite
|
Sign up to set email alerts
|

Spark ignition of propane-air mixtures near the minimum ignition energy: Part I. An experimental study

Abstract: Kernel growth from a spark in propane-air mixtures at atmospheric pressure is studied in a constant volume bomb with a high-speed laser schlieren system. The spark current and voltage waveforms of an inductive ignition source are simultaneously recorded with the photographic recordings. The temporal growth of the measured equivalent radii at conditions near the minimum ignition energy shows the existence of a critical radius and the influence of the critical radius on kernel development. In addition, it is sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(31 citation statements)
references
References 22 publications
2
29
0
Order By: Relevance
“…Previous experiments [10][11][12][13] have studied the evolution of the flame front for mixtures with Lewis numbers near unity. They showed that after the successful formation of a spherical flame front, the flame may propagate to a finite radius and extinguish.…”
Section: Introductionmentioning
confidence: 99%
“…Previous experiments [10][11][12][13] have studied the evolution of the flame front for mixtures with Lewis numbers near unity. They showed that after the successful formation of a spherical flame front, the flame may propagate to a finite radius and extinguish.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of several important applications of localised ignition of inhomogeneous mixtures, a relatively smaller effort has been directed to this area [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] in comparison to the vast body of literature on analytical [17][18][19][20][21][22], experimental [23][24][25][26][27][28][29][30][31][32] and computational [33][34][35][36][37][38] studies on localised ignition of homogenous mixtures. Ballal and Lefebvre [1][2][3] studied the critical spark energy, optimum spark duration and spark radius for successful ignition of inhomogeneous mixtures produced by evaporating droplets in turbulent air flow.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have dealt with ignition studies either experimentally [4,8,9], theoretically using results from high activation energy asymptotic analysis [3][4][5][10][11][12] or numerically [13][14][15][16][17]. Most theoretical and numerical analyses were performed using a zero-dimensional energy balance or one-dimensional models [18] which are restricted to spherical geometries.…”
Section: Introductionmentioning
confidence: 99%